The influence of lower-limb prostheses technology on Paracanoeing time-trial performance - Ellis, S.; Callaway, A.; Dyer, B. (Disability and Rehabilitation: Assistive Technology, 2018)
Within the Paracanoeing discipline, it is important to ensure that appropriate control is achieved by a paddler with a disability. However, this Paralympic Games discipline has seen very little attention to date. The aims of this study were to understand the kinematic impact to a paracanoeist when not utilizing the use of a prosthetic lower-limb. A kayaker with a uni-lateral transfemoral amputation completed several 200 m maximal efforts both with and without their prosthesis. When the prosthetic limb was removed, there were significant differences found in stroke rate, stroke speed, stroke length and overall power output. Sagittal and frontal video analysis demonstrated the residual limb movements when paddling and indicated where support would be required to improve the kayak`s control. It is recommended that those with lower-limb absence wishing to paddle a kayak competitively utilize the use of a prostheses designed for the kayaking environment that supports the residual limb at both the upper and inner thigh and the distal end.